PERAN FILM TOY STORY DALAM TRANSFORMASI ANIMASI DIGITAL DAN PERKEMBANGAN INDUSTRI ANIMASI GLOBAL - Gusti Made Agung Narendra Putra Darma; Labib fauzi; Dionisius Hamonangan Siboro; I Made Hendra Mahajaya Pramayasa (Anima Rupa, 2026)
Toy Story (1995) is an animated film produced by Pixar Animation Studios that became a major milestone in the history of world animation as the first feature-length film created entirely using computer-generated imagery (CGI). This article discusses the history of Toy Story, examines interesting facts behind its production process, and analyzes the film’s impact on the global animation industry. The discussion shows that Toy Story not only introduced technological innovation but also established new standards in animated storytelling by emphasizing emotional depth and character development. Facts such as the inspiration for Buzz Lightyear from astronaut Buzz Aldrin, changes in Woody’s character design, and the role of Pixar’s short film Tin Toy in the creation of Toy Story highlight the complexity of Pixar’s creative process. The success of Toy Story encouraged a major shift from traditional animation to digital animation and had a long-lasting influence on production styles, visual quality, and narrative approaches in modern animated films.